How Organizations Prepare for the Future: A Comparative Study of Firm Size and Industry - Meyer, Tobias; von der Gracht, Heiko A.; Hartmann, Evi (IEEE Transactions on Engineering Management, 2020)
The question of how companies can best prepare for the future to maintain or improve their existing position in the market place has increased its momentum. This article aims to analyze future preparedness as a joint construct consisting of a company's exploitation and exploration capabilities. In this article, we thereby consider exploitation as a firm's strategy to prepare for the future by focusing on its organizational structure and resources, and exploration as its strategy to engage in corporate foresight to anticipate changes in their environment. Previous scholars centered their research on large companies and single industries. In this article, we close this gap by analyzing future preparedness of large companies as well as of small and medium-sized enterprises from 12 different industries. Data were obtained from a heterogeneous sample of 602 companies of the German economy. For data analysis, the measured variables were classified using principal component analysis and compared by means of variance analysis. Our results indicate that companies rather build on exploitation of internal resources than on exploration of their environment. We further present firm size and industry as predictors for future preparedness strategies and found that the scope of future preparedness augments with firm size.<br
Keywords: (Ambidexterity; comparative study; corporate foresight; factor analysis; future preparedness; managerial survey; small and medium-sized enterprise (SMEs); )